Faktor Sosial Budaya (Mitos) Mengenai Personal Hygiene Saat Menstruasi Pada Remaja Perempuan - Evi, Nurul; Dania Uly, Adinda Tiarani; Kurniawati, Amalia Putri; Aulia Putri, Eka Cahyani; Siraj Assauri, Muhammad Dery; Aulia, Syafa Nairah; Nazilah, Yasmin (Universitas Negeri Malang, 2024)
WHO data states that adolescent girls aged 10-14 years from various countries have reproductive health problems, one of which is pruritus vyvae, while data from the Indonesian Central Statistics Agency states that as many as 43.3 adolescent girls aged 10-14 years have very poor hygiene behavior. . Fulfilling self-care can be influenced by various factors, one of which is culture, which in this case is a myth about something that can limit a person's freedom to maintain personal hygiene. Therefore, this article aims to determine social and cultural factors in maintaining personal hygiene or personal hygiene behavior when adolescent girls experience menstruation. This research uses a descriptive method with theoretical references obtained through literature reviews from various scientific literature. Personal hygiene behavior regarding menstruation is influenced by individual beliefs regarding menstruation myths and prohibitions. These individual beliefs can be influenced by the lack of access to information and education received. Insufficient knowledge regarding personal hygiene behavior during menstruation can cause individuals to have limitations in behaving positively towards reproductive health so that it can have a negative impact on physical and emotional well-being. So based on the results obtained, there is a relationship between social culture and personal hygiene behavior in adolescent girls.